Clinical utility of exome sequencing in hearing loss: a retrospective cohort study - Liu, Chang; Huang, Yanlin; Fu, Anpeng; Wang, Yunan; Wu, Jing; Zhang, Yan; Du, Li; Ding, Hongke; Yu, Lihua; Li, Fake; Qi, Yiming; Liu, Yuan; et al. (Frontiers in Genetics, 2025)
BackgroundHearing loss (HL) is a prevalent sensorineural disorder with a highly heterogeneous etiology. Next-generation sequencing (NGS) has revolutionized the genetic testing landscape for diseases characterized by high genetic and allelic heterogeneity, enabling the simultaneous screening of hundreds of genes.MethodsOne hundred and seventy-one unrelated patients with non-syndromic or syndromic HL were enrolled in this study. Exome sequencing (ES) was applied to explore molecular etiology in the cohort, and clinical reports were provided by geneticists and genetic counselors. Multidisciplinary team forums were conducted to ensure accurate diagnoses and improved patient management.ResultsThe molecular cause of HL was determined in 78 of 171 probands (45.6%): 54 with an autosomal recessive (AR) inheritance pattern, 23 with an autosomal dominant (AD) pattern, and 1 with both AR/AD inheritance patterns. Candidate variants in 33 genes were identified in the study cohort: 14 with an AR inheritance pattern, 18 with an AD pattern, and 1 with both AR/AD inheritance patterns. Twenty-eight of the variants identified in the study were novel.ConclusionExome sequencing facilitates genetic diagnosis and improves the management of patients with HL in clinical practice. Identifying the etiology of HL may improve patient care, refine genetic counseling, and facilitate the estimation of recurrence risk.